Grit and the Adult Learner: Should We Be Thinking about Work Ethic? - Joann S. Olson (Adult Education Research Conference, 2015)
Research related to work ethic appears most frequently in psychology and business-related venues, with few publications in education. This roundtable encourages participants to explore whether thinking in terms of a learners’ work ethic is an appropriate or potentially beneficial concept for adult educators.
Keywords: adult learner; work ethic; grit; perseverance